Acute effect of whole-body vibration on sprint and jumping performance in elite skeleton athletes - Bullock, N.; Martin, D. T.; Ross, A.; Rosemond, C. D.; Jordan, M. J.; Marino, F. E. (The Journal of Strength and Conditioning Research, 2008)
The winter sliding sport known as skeleton requires athletes to produce a maximal sprint followed by high speed sliding down a bobsled track. Athletes are required to complete the course twice in 1 hour and total time for the 2 runs determines overall ranking. The purpose of this investigation was to examine the effect of whole-body vibration (WBV) on lower body power to explore the utility of WBV as an ergogenic aid for skeleton competition. Elite skeleton athletes (1 male and 6 females) completed an unloaded squat jump (SQJ) immediately followed by 2 countermovement jumps (CMJs) and a maximal 30-m sprint before and after WBV or no vibration (CON) using a crossover design. The second 30-m sprint was slower following both CON (1.4% decrement; p = 0.05) and WBV (0.7% decrement; p = 0.03). Mean vertical velocity was maintained following WBV in the SQJ but decreased following CON (p = 0.03). There was a trend for athletes to commence the SQJ from a higher starting stance post-WBV compared to CON (p = 0.08). WBV decreased total vertical distance traveled compared to CON in the SQJ (p = 0.006). WBV had little effect on peak velocity, jump height, dip, and peak acceleration or any CMJ parameters. When sprint athletes' warm up and perform maximal jumps and a 30-m sprint with 15-20 minutes of recovery before repeating the sequence, the second series of performances tend to be compromised. However, when WBV is used before the second series of efforts, some aspects of maximal jumping and sprinting appear to be influenced in a beneficial manner. Further research is required to explore whether WBV can improve the second sprint for athletes in actual competition and/or what sort of WBV protocol is optimal for these populations.